Production method for mortar and production method for fresh concrete
A two-step kneading process forms flocs in cement particles to reduce admixture adsorption, enhancing fluidity in mortar and fresh concrete while minimizing admixture use, addressing the cost issue in conventional high-strength concrete production.
Patent Information
- Application Number
- JP2023097465
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2043-06-14
Smart Images

Figure 2024178994000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing mortar and a method for producing fresh concrete. [Background technology]
[0002] Concrete, a building material, is made by mixing the main ingredients of fine aggregate (sand), coarse aggregate (gravel), cement, and mixing water in a mixer, etc. Fresh concrete (ready-mixed concrete) has fluidity immediately after production, but as time passes, the hydration reaction progresses and it eventually hardens.
[0003] The mix ratio of concrete varies depending on the application, but the ratio of cement to mixing water affects the strength after hardening. In recent years, there has been an increase in demand for high-strength concrete, which is used for the columns of skyscrapers and civil engineering structures. High-strength concrete is a high-powder mix, with a relatively small amount of mixing water compared to the amount of cement.
[0004] In the case of such a high powder mix, the fluidity of fresh concrete tends to be low. However, when using fresh concrete, there are requirements for handling, such as pumping, so it is necessary to ensure at least the fluidity required during construction.
[0005] Therefore, when producing high-strength concrete, a certain amount of a chemical called an admixture (a type of surfactant) is added to ensure the fluidity of fresh concrete. A conventional technique for producing high-strength concrete using an admixture is described in, for example, Patent Document 1. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 2-107543 Summary of the Invention [Problem to be solved by the invention]
[0007] In the conventional method of producing fresh concrete using admixtures, fine aggregate, cement, mixing water, and admixtures are all charged into a mixer at once. Then, the fine aggregate, cement, mixing water, and admixtures are mixed in the mixer to produce mortar. After that, coarse aggregate is added to the mixer and further mixed to produce fresh concrete.
[0008] However, in the conventional method of ensuring fluidity by relying only on the addition of admixtures, if the desired fluidity cannot be obtained depending on the mixing conditions, the amount of admixture must be increased, which increases the cost of the admixture and raises the price of high-strength concrete.
[0009] The present invention has been made in consideration of the above problems, and has an object to provide a method capable of improving the fluidity of mortar or fresh concrete while suppressing the amount of admixture used. [Means for solving the problem]
[0010] In order to solve the above problems, the first invention of the present application is a method for producing mortar, comprising a first mixing step of mixing fine aggregate containing water with cement, and a second mixing step of adding mixing water and an admixture and further mixing the mixture after the first mixing step.
[0011] A second invention of the present application is the manufacturing method of the first invention, wherein the cement particles form flocs in the first kneading step.
[0012] A third invention of the present application is the production method of the first or second invention, wherein the kneading time in the first kneading step is 30 seconds or more.
[0013] The fourth invention of the present application is a manufacturing method according to any one of the first to third inventions, wherein the surface water ratio of the fine aggregate is 2% or more and 5% or less in the surface water ratio test method specified in JIS A 1111:2015.
[0014] A fifth aspect of the present invention is the manufacturing method according to any one of the first to fourth aspects, in which a mixing time in the first mixing step is adjusted according to a surface water ratio of the fine aggregate.
[0015] A sixth invention of the present application is a manufacturing method of the fifth invention, in which the kneading times of the first kneading step and the second kneading step are adjusted so that the longer the kneading time of the first kneading step, the shorter the kneading time of the second kneading step.
[0016] The seventh invention of the present application is a method for producing fresh concrete including the producing method of the first invention or the second invention, and has the first kneading step and the second kneading step, and a third kneading step in which coarse aggregate is added and further mixing is performed after the second kneading step. Effect of the Invention
[0017] According to the first to seventh inventions of the present application, in the first mixing step, the cement particles form flocs due to the water contained in the fine aggregate. This reduces the specific surface area of the cement, and in the second mixing step, excess admixture is generated that is not adsorbed to the cement particles and remains. This excess admixture contributes to improving the fluidity of the mortar. Therefore, the fluidity of the mortar can be improved while suppressing the amount of admixture used.
[0018] In particular, according to the third aspect of the present invention, the formation of flocs is promoted in the first kneading step, which can further improve the fluidity of the mortar.
[0019] In particular, according to the fourth aspect of the present invention, by setting the surface water ratio of the fine aggregate to 2% or more, the cement particles form flocs well (for example, at an appropriate size). Also, by setting the surface water ratio of the fine aggregate to 5% or less, it is possible to prevent the flocs from becoming excessively thick in the first kneading step. As a result, it is possible to shorten the kneading time in the second kneading step.
[0020] In particular, according to the fifth aspect of the present invention, the mixing time in the first mixing step can be optimized in accordance with the surface water ratio of the fine aggregate so that the cement particles can satisfactorily form flocs.
[0021] In particular, according to the sixth aspect of the present invention, even if the kneading time in the first kneading step is long, the total time of all steps can be prevented from increasing.
[0022] In particular, according to the seventh aspect of the present invention, the excess admixture generated in the second mixing step contributes to improving the fluidity of the fresh concrete. Therefore, the fluidity of the fresh concrete can be improved while suppressing the amount of admixture used. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a schematic diagram of a manufacturing apparatus for manufacturing fresh concrete. [Diagram 2] 1 is a flowchart showing a procedure for producing fresh concrete. [Diagram 3] FIG. 2 is a schematic diagram showing the state of cement particles in a first kneading step. [Figure 4] FIG. 4 is a diagram showing a schematic view of a second kneading step. [Diagram 5] FIG. 1 is a diagram showing the mix proportions of high-strength concrete. [Figure 6] FIG. 13 is a diagram showing conditions of a first test. [Figure 7] 1 is a graph showing the results of a first test. [Figure 8] 13 is a graph showing the results of a second test. [Figure 9] 13 is a graph showing the results of a third test. [Figure 10] 13 is a graph showing the results of a fourth test (measurement results of color absorbance). [Figure 11] 13 is a graph showing the results of the fourth test (measurement results of water absorbance). [Figure 12] FIG. 13 shows the results of the fifth test. [Figure 13] 13 is a graph showing the results of the sixth test. [Figure 14] 13 is a graph showing the results of the seventh test. [Figure 15] FIG. 13 shows the results of the eighth test. [Figure 16] 1 is an image of the material taken with a scanning electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings.
[0025] <1. Mixer configuration> 1 is a schematic diagram of a manufacturing apparatus 1 for manufacturing fresh concrete (ready mixed concrete). As shown in FIG. 1, the manufacturing apparatus 1 includes a mixer body 10, a blade 20, a motor 30, a material supply device 40, and a control unit 50.
[0026] The mixer body 10 is a container capable of containing materials for fresh concrete. The blades 20 are disposed within the mixer body 10. The ends of the blades 20 are connected to a motor 30. When the motor 30 is operated, the blades 20 rotate due to the power output from the motor 30. This allows the materials contained within the mixer body 10 to be mixed.
[0027] In the example of Fig. 1, two blades 20 rotating around a horizontal shaft 21 are arranged inside the mixer body 10. However, the number of blades 20 and the orientation of the shaft 21 are not limited to the example of Fig. 1.
[0028] The material supply device 40 is a device that supplies materials for fresh concrete into the mixer body 10. The material supply device 40 is composed of a weighing device, a hopper, etc. The material supply device 40 can supply fine aggregate, cement, mixing water, admixtures, and coarse aggregate, which will be described later, to the mixer body 10 at designated times and in designated amounts, respectively, according to control signals input from the control unit 50.
[0029] The control unit 50 is a unit that controls the operation of the motor 30 and the material supply device 40. The control unit 50 is composed of a computer having a processor such as a CPU, a memory such as a RAM, and a storage unit such as a hard disk drive. The control unit 50 outputs control signals to the motor 30 and the material supply device 40 according to a computer program and various set values. As a result, the material is supplied from the material supply device 40 to the mixer body 10, and the blades 20 rotate in the mixer body 10 to mix the material.
[0030] <2. Manufacturing method> Next, in the manufacturing device 1, high-strength concrete (design standard strength defined by the Architectural Institute of Japan is 36 N / mm 2 A method for producing fresh concrete for the above concrete) will be described. Fig. 2 is a flow chart showing the procedure for producing fresh concrete. The procedure in Fig. 2 is realized by the above-mentioned control unit 50 controlling the operation of the motor 30 and the material supply device 40.
[0031] When producing fresh concrete, first, fine aggregate and cement are supplied from the material supply device 40 to the mixer body 10. The fine aggregate is aggregate with a smaller particle size than the coarse aggregate described later. For example, natural sand (sea sand, mountain sand), crushed sand, crushed lime sand, etc. are used as the fine aggregate. Note that the crushed sand conforming to JIS A 5005:2009 is preferably used, and the natural sand conforming to JIS A 5308:2019 is preferably used. The fine aggregate may be recycled aggregate (recycled fine aggregate), slag-based fine aggregate, or other alternative aggregate (alternative fine aggregate). The fine aggregate is not used in an absolute dry state, but contains water (surface water) on the surface. For example, normal cement, early strength cement, moderate heat cement, low heat cement, etc. are used as the cement.
[0032] Next, the motor 30 rotates the blades 20 to mix the fine aggregate and cement in the mixer body 10 (first mixing step S1). This first mixing step S1 is a step in which mixing (dry mixing) is performed only with the fine aggregate and cement without adding mixing water or admixture. The mixing time in the first mixing step S1 is preferably, for example, 30 to 90 seconds.
[0033] FIG. 3 is a schematic diagram showing the state of cement particles in the first kneading step S1. When fine aggregate and cement are kneaded in the first kneading step S1, the surface water of the fine aggregate comes into contact with the cement particles. Then, due to the action of water moving from the surface of the fine aggregate to the cement particles, the cement particles aggregate with each other as shown in FIG. 3 to form flocs F. Flocs F are aggregates of about 10 to several tens of μm and have an average particle size equal to or larger than the average particle size of cement particles (about 10 μm). When the cement particles form flocs F in this way, the specific surface area of the cement becomes smaller compared to a state in which flocs F are not formed. The mechanism by which flocs F are formed is, for example, that when water is added to cement, a positive charge is generated on the surface of the cement particles due to a hydration reaction, making the cement unstable, and the particles stick together.
[0034] The mixing time (dry mixing) in the first mixing step S1 is preferably a predetermined time or more that allows the cement particles to form flocs F and suppresses the specific surface area of the cement particles compared to when dry mixing is not performed. For example, by continuing the mixing (dry mixing) in the first mixing step S1 for 30 seconds or more, the growth of the flocs F of the cement particles can be promoted and the specific surface area can be sufficiently reduced (a significant difference in the specific surface area can be achieved) compared to when dry mixing is not performed. As a result, as described later, the amount of admixture remaining in the liquid phase without being adsorbed to the cement particles can be sufficiently increased (a significant difference in the amount of adsorption can be achieved) compared to when dry mixing is not performed.
[0035] When the first mixing step S1 is completed for a predetermined time, the material supply device 40 then adds mixing water (water) and admixtures to the mixer body 10. Then, the motor 30 continues to rotate the blades 20 to further mix the materials (second mixing step S2). As a result, mortar consisting of fine aggregate, cement, water, and admixtures is produced.
[0036] The admixture may be a water-reducing agent, which is a type of surfactant, a high-performance water-reducing agent, or a combination of these. The admixture may be, for example, a polycarboxylic acid-based water-reducing agent having a steric hindrance effect, or a naphthalene-based water-reducing agent or a melamine-based water-reducing agent having an electrostatic repulsion effect, as its main component. The base of the admixture may be, for example, polystyrene sulfonate, polycarboxylate, naphthalene sulfonate, or melamine sulfonate.
[0037] FIG. 4 is a schematic diagram showing the second kneading step S2. The admixture adsorbs to the cement particles and repels the cement particles from each other. However, in the manufacturing method of this embodiment, the cement particles form flocs F in the first kneading step S1, so the specific surface area of the cement is small. Therefore, the amount of admixture adsorbed to the cement particles is smaller than when the flocs F are not formed. As a result, in this second kneading step S2, some of the admixtures added are not adsorbed to the cement particles and remain as excess admixtures. This excess admixture contributes to improving the fluidity of the mortar.
[0038] When the second mixing step S2 for a predetermined time is completed, the material supply device 40 then adds coarse aggregate (gravel) to the mixer body 10. The coarse aggregate is aggregate with a larger particle size than the above-mentioned fine aggregate. For example, crushed stone or natural gravel (river gravel, etc.) is used as the coarse aggregate. Then, further mixing is performed by continuing to rotate the blades 20 by the motor 30 (third mixing step S3). As a result, fresh concrete consisting of fine aggregate, cement, water, admixture, and coarse aggregate is generated.
[0039] As described above, some of the admixtures added in the second mixing step S2 remain as excess admixtures without being adsorbed by the cement particles. This excess admixture improves the fluidity of the mortar produced in the second mixing step S2 and the fresh concrete produced in the third mixing step S3.
[0040] That is, according to the manufacturing method of this embodiment, by performing the first kneading step S1, the cement particles form flocs F, and the specific surface area of the cement decreases. This reduces the amount of admixture adsorption in the second kneading step S2. Therefore, even if a large amount of admixture is not used, it is possible to generate surplus admixture that is not adsorbed to the cement particles in the early stage of the second kneading step S2. Then, the surplus admixture improves the fluidity of the mortar produced in the second kneading step S2 and the fresh concrete finally produced in the third kneading step S3. Therefore, it is possible to improve the fluidity of the mortar and the fresh concrete while suppressing the amount of admixture used.
[0041] At least a part of the floc F generated in the second kneading step S2 may be decomposed into a plurality of cement particles in the third kneading step S3. However, it is considered that the decomposed cement particles are also well dispersed by adsorption of the surplus admixture described above. Alternatively, in the second kneading step S2 and the third kneading step S3, the mixing water and the cement particles come into contact with each other to sequentially generate hydration products. If the admixture already adsorbed to the cement particles (or hydration products) is taken in by these hydration products, the dispersing effect of the admixture is weakened. However, it is considered that the surplus admixture described above is sequentially adsorbed to the surface of the newly generated hydration products, thereby maintaining these hydration products in a dispersed state. As a result of these, it is considered that the fluidity of fresh concrete can be improved compared to the case where there is no surplus admixture.
[0042] The surface water ratio of the fine aggregate added in the first mixing step S1 is preferably 2% or more and 5% or less according to the surface water ratio test method specified in JIS A 1111:2015. By making the surface water ratio of the fine aggregate 2% or more, the cement particles form flocs F well (at a suitable size of about 10 to several tens of μm) in the first mixing step S1. In addition, excessively enlarged flocs F impair the fluidity of fresh concrete (flocs F enlarged to the extent that they become a factor inhibiting the development of fluidity are hereinafter referred to as "lumps"). However, by making the surface water ratio of the fine aggregate 5% or less, the generation of such lumps can be suppressed in the first mixing step S1. As a result, the mixing time required to break up the lumps in the second mixing step S2 or the third mixing step S3 can be shortened.
[0043] The mixing time in the first mixing step S1 may be adjusted according to the surface water ratio of the fine aggregate. For example, the surface water ratio of the fine aggregate may be input to the control unit 50, and the control unit 50 may set the mixing time based on the input surface water ratio. Specifically, when the surface water ratio of the fine aggregate is higher than a predetermined value, the mixing time in the first mixing step S1 may be set longer. As described above, when the surface water ratio of the fine aggregate is higher than a predetermined value, lumps of cement particles are likely to be generated during dry mixing, and if such lumps remain in the subsequent mixing step, they will rather impair the fluidity of the fresh concrete. In this case, by setting the mixing time in the first mixing step S1 to be longer, the generated lumps can be broken down. This allows the mixing time in the first mixing step S1 to be optimized so that the flocs F are generated well (with an appropriate size of about 10 to several tens of μm). For example, when the surface water content of the fine aggregate is 4% or more, the mixing time in the first mixing step S1 is preferably set to 60 seconds or more.
[0044] In addition, a sensor for measuring the surface water ratio of the fine aggregate may be provided in the manufacturing apparatus 1, and the measured value of the surface water ratio may be input to the control unit 50 from the sensor.
[0045] Furthermore, when adjusting the kneading time of the first kneading step S1 as described above, the kneading times of the first kneading step S1 and the second kneading step S2 may be adjusted so that the longer the kneading time of the first kneading step S1, the shorter the kneading time of the second kneading step S2. Also, the sum of the kneading time of the first kneading step S1 and the kneading time of the second kneading step S2 may be kept constant. In this way, even if the kneading time of the first kneading step S1 is long, the total time of all steps can be prevented from being extended.
[0046] <3. Test> <3-1. Common conditions for the 1st test to the 7th test> In order to demonstrate the effect of the above manufacturing method, the first to seventh tests were carried out on mortar. 2 The materials for high-strength concrete were used. The mix proportions for the high-strength concrete are shown in Figure 5. The amount of admixture added to the cement amount was 0.6%. The materials were mixed using a Hobart mixer (5 liters). Each test was carried out in a room with a constant environment of 20±2°C temperature and humidity of 50% or more.
[0047] <3-2. First test> A first test was carried out to examine the effect of the presence or absence of the first kneading step S1 on the fluidity of the mortar.
[0048] Fig. 6 is a diagram showing the conditions of the first test. In the example in Fig. 6, fine aggregate with a surface water ratio of 3% was mixed with cement, and then mixing water and admixtures were added and further mixing was performed. In the first comparative example in Fig. 6, fine aggregate in an absolute dry state was mixed with cement, and then mixing water and admixtures were added and further mixing was performed. In the second comparative example in Fig. 6, fine aggregate, cement, mixing water, and admixtures were mixed without previously mixing only fine aggregate and cement.
[0049] In the examples and the first comparative example, the mixing time of the fine aggregate and cement was 30 seconds. In the examples, the first comparative example, and the second comparative example, the total mixing time was set to 3, 4, 7, 10, 15, and 20 minutes to produce mortars, and the flow value indicating the fluidity of each of the obtained mortars was measured using the test method described in JIS R 5201:2015.
[0050] FIG. 7 is a graph showing the results of the first test. The horizontal axis of FIG. 7 indicates the total mixing time. The vertical axis of FIG. 7 indicates the flow value of the generated mortar. After 7 minutes, when mixing is considered to be completed, the flow value of the example is higher than the flow values of the first and second comparative examples. Even if the mixing time is further increased beyond 7 minutes, the flow values of the first and second modified examples do not reach the flow value of the example. A substantially constant difference (about 8 cm) is maintained between the flow value of the example and the flow values of the first and second modified examples. From this result, it can be seen that the flow value of the mortar is improved by performing the first mixing step S1 with fine aggregate containing water and cement, as in the example.
[0051] Also, according to the results in Fig. 7, the flow values are almost the same for the first comparative example, in which dry mixing was performed similarly to the first mixing step S1 using bone-dry fine aggregate, and the second comparative example, in which dry mixing was not performed. The only difference between the working example and the first comparative example is whether or not the fine aggregate contains water. This shows that the contact of the water contained in the fine aggregate with the cement particles in the first mixing step S1 contributes to an improvement in the flow value.
[0052] <3-3. Second test> A second test was conducted to investigate the difference in flow values with and without admixture.
[0053] FIG. 8 is a graph showing the results of the second test. The Example and the Second Comparative Example in FIG. 8 show the case where mixing was performed under the same conditions as the Example and the Second Comparative Example in the first test described above. The Third Comparative Example in FIG. 8 shows the case where mixing was performed under the same conditions as the Example except for the addition of the admixture. The Fourth Comparative Example in FIG. 8 shows the case where mixing was performed under the same conditions as the Second Comparative Example except for the addition of the admixture. In the second test, the total mixing time was 7 minutes. The vertical axis in FIG. 8 shows the flow value of the generated mortar.
[0054] As in the first test, in the second test, the flow value of the embodiment is about 8 cm higher than that of the second comparative example. On the other hand, the flow value of the third comparative example and the flow value of the fourth comparative example are almost the same. That is, when a compatibilizing agent is added, the flow value differs depending on whether or not the first kneading step S1 is performed, but when a compatibilizing agent is not added, there is no difference in the flow value depending on whether or not the first kneading step S1 is performed.
[0055] This shows that adding admixtures in the second mixing step S2 after the water contained in the fine aggregate comes into contact with the cement particles in the first mixing step S1 to cause initial hydration contributes to improving the flow value.
[0056] <3-4. Third test> A third test was carried out to examine the effect of the mixing time in the first mixing step S1 (hereinafter referred to as "dry mixing time") on the fluidity of the mortar.
[0057] In the third test, the first kneading step S1 and the second kneading step S2 were performed under the same conditions as in the above-mentioned example. However, the dry kneading time in the first kneading step S1 was set to four patterns of 0, 30, 60, and 90 seconds. In addition, the total kneading time in the first kneading step S1 and the second kneading step S2 was fixed at 7 minutes. Then, the flow value of the mortar generated by the first kneading step S1 and the second kneading step S2 was measured by the test method specified in JIS R 5201:2015.
[0058] FIG. 9 is a graph showing the results of the third test. The horizontal axis of FIG. 9 indicates the dry mixing time. The vertical axis of FIG. 9 indicates the flow value of the produced mortar. According to the results of FIG. 9, the longer the dry mixing time, the higher the flow value of the produced mortar. From this result, it can be seen that the flow value of the mortar improves by increasing the contact time between the surface water of the fine aggregate and the cement before adding the admixture.
[0059] <3-5. Fourth Test> A fourth test was conducted to investigate the relationship between dry mixing time and the amount of water transferred from fine aggregate to cement particles.
[0060] In the fourth test, a cement substitute was used, with a density of 2.71 g / cm 3 Calcium carbonate was used in order to evaluate the amount of pure water that moves from the fine aggregate to the powder by suppressing the reaction with water. The particle size of calcium carbonate is sufficiently smaller than that of the fine aggregate, so the difference in physical properties between cement and calcium carbonate is considered to be negligible when evaluating the amount of water that moves. In the fourth test, fine aggregate in an absolute dry state was used to which water colored with food coloring was attached in order to accurately evaluate the amount of water that moves. The surface water rate of the fine aggregate was set to 3%.
[0061] After mixing the fine aggregate and calcium carbonate (dry mixing), the absorbance of the color wavelength (color absorbance) and the absorbance of the water wavelength (water absorbance) of the surface of the material were measured multiple times using an infrared multi-component meter. The dry mixing time was set to three patterns: 30, 60, and 90 seconds.
[0062] Fig. 10 is a graph showing the measurement results of color absorbance. Fig. 11 is a graph showing the measurement results of water absorbance. The horizontal axis of Fig. 10 and Fig. 11 indicates the dry mixing time. The vertical axis of Fig. 10 and Fig. 11 indicates the absorbance. The larger the absorbance value, the wider the area exhibiting that wavelength, that is, the greater the amount of water that moves from the fine aggregate to the calcium carbonate.
[0063] In both the results of Figures 10 and 11, the longer the dry mixing time, the higher the absorbance. Therefore, in both the results of Figures 10 and 11, it can be seen that the longer the dry mixing time of fine aggregate and calcium carbonate, the more water moves from the fine aggregate to the calcium carbonate. Therefore, when mixing fine aggregate and cement, it is thought that the longer the dry mixing time, the more water moves from the fine aggregate to the cement particles.
[0064] <3-6. Fifth Test> The fifth test was conducted to examine the relationship between the dry mixing time and the amount of floc F formed.
[0065] In the fifth test, fine aggregate with a surface water ratio of 3% was mixed with cement. The mixing time was set to two patterns, 30 seconds and 90 seconds. The mixed material was then sieved, and the weight of the material that passed through the sieve and the weight of the material that remained on the sieve were measured. The sieve used had a mesh opening diameter of 0.15 mm.
[0066] Figure 12 shows the results of the fifth test. According to the results in Figure 12, the longer the dry mixing time, the less the weight of the material that passes through the sieve and the more the weight of the material that remains on the sieve. When fine aggregate and cement are mixed and the cement comes into contact with the surface water of the fine aggregate, the cement particles aggregate together due to the electric charge generated by the hydration reaction, forming flocs F. The longer the dry mixing time, the greater the amount of flocs F that are formed.
[0067] The results in Fig. 12 are considered to be correlated with the formation of such flocs F. In the eighth test described below, we succeeded in acquiring images of flocs F.
[0068] <3-7. 6th Test> A sixth test was conducted to examine the amount of admixture adsorbed to the cement particles in the second mixing step S2.
[0069] In the sixth test, the first kneading step S1 and the second kneading step S2 were performed under the same conditions as in the above-mentioned example. However, the dry kneading time in the first kneading step S1 was set to three patterns of 0, 30, and 90 seconds. In addition, the total kneading time in the first kneading step S1 and the second kneading step S2 was fixed to 7 minutes. Then, the mortar generated by the first kneading step S1 and the second kneading step S2 was separated into a liquid phase and a solid phase using a centrifuge, and the amount of the admixture in the liquid phase was measured by thermally analyzing the obtained liquid phase.
[0070] FIG. 13 is a graph showing the results of the sixth test. The horizontal axis of FIG. 13 indicates the number of measurements. The vertical axis of FIG. 13 indicates the concentration of the admixture in the liquid phase. According to the results of FIG. 13, when the dry-mixing time is 0 seconds, the amount of admixture remaining in the liquid phase is small, and as the dry-mixing time increases, the amount of admixture remaining in the liquid phase increases. From this, it can be seen that when the dry-mixing time is short, the amount of admixture adsorbed to the solid phase (i.e., cement particles) is large, and as the dry-mixing time increases, the amount of admixture adsorbed to the solid phase decreases.
[0071] <3-8. Seventh Test> The seventh test was conducted to investigate the relationship between the dry mixing time and the amount of hydration reaction of cement and mixing water.
[0072] In the seventh test, the first kneading step S1 and the second kneading step S2 were performed under the same conditions as in the above-mentioned examples. However, the dry kneading time in the first kneading step S1 was set to three patterns of 0, 30, and 90 seconds. In addition, the total kneading time in the first kneading step S1 and the second kneading step S2 was fixed to 7 minutes. Then, the mortar generated in the first kneading step S1 and the second kneading step S2 was separated into a liquid phase and a solid phase using a centrifuge, and the obtained solid phase was analyzed by an X-ray diffraction device to measure the amount of ettringite generated during the hydration reaction of cement.
[0073] FIG. 14 is a graph showing the results of the seventh test. The horizontal axis of FIG. 14 indicates the diffraction angle of X-rays. The vertical axis of FIG. 14 indicates the intensity of X-rays. Since the peak value of the diffraction angle of ettringite is 8.7 to 9.4°, the integral value of the intensity (integral intensity) in the range of 8.7 to 9.4° was calculated and compared in the graph of FIG. 14. According to the results of FIG. 14, when the dry mixing time is 0 seconds, the integral intensity is large, and as the dry mixing time becomes longer, the integral intensity becomes smaller. That is, when the dry mixing time is 0 seconds, the amount of ettringite generated is large, and as the dry mixing time becomes longer, the amount of ettringite generated decreases.
[0074] This result is believed to be due to the fact that when the dry mixing time is short, the amount of floc F formed is small, resulting in a large amount of hydration reaction between the cement and mixing water, but as the dry mixing time is longer, the amount of floc F formed increases, resulting in a smaller amount of hydration reaction between the cement and mixing water.
[0075] <3-9.Summary> From the results of the first to seventh tests, the following can be seen. That is, by performing the first kneading step S1, water on the surface of the fine aggregate moves to the cement particles, and the cement particles form flocs F. Then, the specific surface area of the cement decreases due to the flocs F, and the amount of admixture adsorbed to the cement decreases in the second kneading step S2. This results in an increase in the amount of surplus admixture remaining without being adsorbed to the cement. Then, due to the influence of the surplus admixture, the flow value of the generated mortar increases. Therefore, by performing the first kneading step S1, it is possible to improve the fluidity of the mortar without using a large amount of admixture.
[0076] In addition, by performing the first mixing step S1, the excess admixture continues to exist not only in the second mixing step S2 but also in the third mixing step S3 that follows the second mixing step S2. Therefore, it is considered that the fluidity of the fresh concrete produced in the third mixing step S3 can also be improved. Therefore, it is considered that the fluidity of the fresh concrete can also be improved by performing the first mixing step S1 without using a large amount of admixture.
[0077] In the above first to seventh tests, materials with a specific mix were used, but even when materials with other mixes are used, it is believed that by performing the first mixing step S1, cement flocs F are formed in the same manner and the specific surface area of the cement is reduced. Therefore, even when materials with other mixes are used, it is believed that excess admixtures are produced in the second mixing step S2, which can have the effect of improving the fluidity of mortar and fresh concrete.
[0078] <3-10. 8th Test> Next, the eighth test was conducted on fresh concrete, which was made by adding and mixing coarse aggregate after the mortar was produced. In this test, as in the previous test, the design strength was 80 N / mm 2 The materials for high-strength concrete were used. The mix proportions for this high-strength concrete are shown in Figure 5. The amount of admixture added to the cement amount was 0.6%. However, in this 8th test, the materials were mixed using a two-axis forced mixing test mixer (60 liters), which is closer to the actual conditions of the plant. The test was carried out indoors in a constant environment with a temperature of 20±2°C and a humidity of 50% or more.
[0079] In the eighth test, the dry mixing time in the first mixing step S1 was set to two patterns, 30 seconds and 90 seconds. The total mixing time in the first mixing step S1 and the second mixing step S2 was fixed to 7 minutes. The flow value of the mortar generated in the first mixing step S1 and the second mixing step S2 was measured by the test method specified in JIS R 5201:2015. In the eighth test, fresh concrete was generated by further adding coarse aggregate to the generated mortar and performing the third mixing step S3. The mixing time in the third mixing step S3 was set to 3 minutes. The flow value of the fresh concrete generated in the third mixing step S3 was measured by the test method specified in JIS A 1150:2007.
[0080] FIG. 15 is a diagram showing the results of the eighth test. As shown in FIG. 15, in the eighth test, the flow value of the mortar when the dry mixing time was 90 seconds was improved compared to the flow value of the mortar when the dry mixing time was 30 seconds. However, the difference in flow value was about 3 cm, and the improvement in the flow value of the mortar itself was smaller than the result of the third test using the Hobart mixer. On the other hand, for the fresh concrete obtained by adding gravel to the mortar and performing the third mixing step S3, the flow value when the dry mixing time was 90 seconds was improved by 20 cm or more compared to the flow value when the dry mixing time was 30 seconds. In other words, the flow value of the fresh concrete was significantly improved by dry mixing. In addition, when the amount of admixture in the liquid phase was also tested in the same manner as in the sixth test, it was confirmed that more admixture remained when the dry mixing time was 90 seconds.
[0081] Figure 16 shows images of the material after mixing in the second mixing process taken with a biaxial forced mixing test mixer using a scanning electron microscope (SEM). In the example of Figure 16, the cement area identified by mapping in a 250x image is shown enlarged to a 500x image. In the 500x image, when comparing the dry mixing time of 30 seconds with that of 90 seconds, the particle diameter is larger overall in the 90 second case. This shows that the longer the dry mixing time, the more the formation of Floc F progresses. Therefore, it can be considered that by extending the dry mixing time, more of the admixture remains in the liquid phase due to the formation and growth of Floc F, which contributes to improving the final flow value of fresh concrete.
[0082] <3-11.Summary> From the results of the eighth test, it was found that even under conditions close to those of an actual machine (two-axis forced mixing test mixer), the flow value of the mortar itself is slightly improved by extending the dry mixing time, and the final flow value of the fresh concrete after adding coarse aggregate is significantly improved. In this case, although the effect of improving the flow value of the mortar itself by extending the dry mixing time seems small at first glance, the growth of floc F in the mortar is promoted, and a difference in properties not reflected in the flow value occurs when compared with mortars with short dry mixing times (or mortars without dry mixing). Therefore, it can be concluded that by extending the dry mixing time, it is possible to produce mortars with properties that are favorable for the final expression of the flow value of fresh concrete. It is also considered that floc F is formed in a roughly similar manner when dry mixing is performed with the Hobart mixer (as mentioned above, it is inferred that floc F is formed from the amount of material passing through the 0.15 mm sieve and the amount of admixture remaining in the liquid phase, etc.).
[0083] In the eighth test using the twin-axis forced mixing test mixer, the degree of improvement in the flow value of the mortar itself with the extension of the dry mixing time was smaller than that in the experimental results using the Hobart mixer. This is presumably due to mechanical differences or differences in mixing volume. As described above, the inventors obtained electron microscope images of Floc F as a difference in mortar properties that is not reflected in the flow value. As the dry mixing time is extended, Floc F in the mortar grows, and more admixtures remain in the liquid phase. In the twin-axis forced mixing test mixer, the fluidity improving effect of the remaining admixtures becomes even more pronounced after the coarse aggregate is added, and it is possible to finally achieve a high flow value in fresh concrete.
[0084] In Japan, many fresh concrete manufacturing plants use twin-shaft forced mixers (mixing capacity is 0.5 m 3 ~6.0m 3 , or more), and therefore, based on the results of the eighth test, it is believed that even under the conditions of an actual machine such as a large twin-shaft forced mixing mixer, the final flow value (fluidity) of fresh concrete will be fully realized at the completion of the third mixing step S3, in which coarse aggregate is added and further mixing is performed.
[0085] <4.Other> The present invention is not limited to the above-described embodiments. Some of the elements appearing in the above-described embodiments may be deleted or combined without departing from the spirit of the present invention. [Industrial Applicability]
[0086] The present invention can be used in a method for producing mortar or concrete. [Explanation of symbols]
[0087] 1 Manufacturing equipment 10 Mixer body 20 Feather 21 Axis 30 Motor 40 Material supply device 50 Control section F Frock S1 First kneading process S2 2nd kneading process S3 Third kneading process
Claims
1. A method for producing mortar, comprising the steps of: A first mixing step of mixing water-containing fine aggregate and cement; A second kneading step in which mixing water and an admixture are added after the first kneading step and further kneading is performed; The manufacturing method comprising the steps of:
2. The method according to claim 1, The method for producing a cement composition, comprising the steps of: forming flocs of the cement particles in the first kneading step;
3. The method according to claim 1 or 2, The manufacturing method, wherein the kneading time in the first kneading step is 30 seconds or more.
4. The method according to claim 1 or 2, A manufacturing method in which the surface water ratio of the fine aggregate is 2% or more and 5% or less, according to the surface water ratio test method specified in JIS A 1111:2015.
5. The method according to claim 1 or 2, The manufacturing method includes adjusting a mixing time in the first mixing step depending on a surface water content of the fine aggregate.
6. The method according to claim 5, The manufacturing method includes adjusting the kneading times in the first kneading step and the second kneading step such that the longer the kneading time in the first kneading step, the shorter the kneading time in the second kneading step.
7. A method for producing fresh concrete, comprising the method according to claim 1 or 2, The first kneading step and the second kneading step, A third kneading step in which coarse aggregate is added and further kneaded after the second kneading step; The manufacturing method comprising the steps of:
Citation Information
Patent Citations
Manufacture of product by hydraulic substance
JP1983201608A
Manufacture of concrete
JP1986199910A
Method of mixing cocrete
JP1987039206A
Method of placing high-durability concrete
JP1987173216A
Kneading method of concrete-mortar
JP1987199407A
